2017
DOI: 10.1371/journal.pone.0169429
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Stroke and Post-Stroke Adverse Events in Patients with Exacerbations of Chronic Obstructive Pulmonary Disease

Abstract: BackgroundThe risk and outcomes of stroke in patients with chronic obstructive pulmonary disease exacerbations (COPDe) remain unclear. We examined whether patients with COPDe faced increased risk of stroke or post-stroke outcomes.MethodsUsing Taiwan’s National Health Insurance Research Database, we identified 1918 adults with COPDe and selected comparison cohorts of 3836 adults with COPD no exacerbations and 7672 adults without COPD who were frequency matched by age and sex in 2000–2008 (Study 1). Stroke event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…However, in a study using Taiwan's National Health Insurance Research Database, a comparison cohort of 1918 adults with COPD exacerbations, 3836 adults with COPD no exacerbations, and 7672 adults without COPD who were frequency matched by age and sex, were selected. 84 Patients with exacerbations had increased stroke incidence (adjusted HR 1.28, 95% CI 1.03-1.59) and post-stroke mortality (OR 1.34, 95% CI 1.20-1.52) and complications, including, epilepsy and pneumonia. In a study that assessed the prevalence of COPD among hospitalized stroke patients in the National Inpatient Sample, a nationally representative dataset of US hospital admissions between January 2004 and December 2009, 12% of the hospitalized stroke patients have COPD.…”
Section: Primary Studiesmentioning
confidence: 95%
“…However, in a study using Taiwan's National Health Insurance Research Database, a comparison cohort of 1918 adults with COPD exacerbations, 3836 adults with COPD no exacerbations, and 7672 adults without COPD who were frequency matched by age and sex, were selected. 84 Patients with exacerbations had increased stroke incidence (adjusted HR 1.28, 95% CI 1.03-1.59) and post-stroke mortality (OR 1.34, 95% CI 1.20-1.52) and complications, including, epilepsy and pneumonia. In a study that assessed the prevalence of COPD among hospitalized stroke patients in the National Inpatient Sample, a nationally representative dataset of US hospital admissions between January 2004 and December 2009, 12% of the hospitalized stroke patients have COPD.…”
Section: Primary Studiesmentioning
confidence: 95%
“…Cigarette smoking is also a major cause of chronic obstructive pulmonary disease (COPD), accounting for more than 95% of cases in industrialized countries 5 . Recent studies have shown that strokes are more prevalent in COPD patients compared with the general population 68 , and clinical studies have revealed that COPD is linked to worse stroke outcomes including mortality 9,10 . Given smoking is an established risk factor for stroke and is linked to worse stroke outcomes the association between COPD and stroke may be largely dependent on exposure to cigarette smoke 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show that the risk of stroke is 20% greater in COPD patients compared to the general population, and this risk is estimated to be 7-fold higher following an exacerbation of COPD [ 21 , 22 ]. There is also some evidence to suggest that there is a relationship between COPD and worse stroke outcomes such as mortality, pneumonia, epilepsy, length of hospital stay and also intensive care unit care [ 23 ]. COPD is an independent risk factor for mortality among patients with stroke [ 24 ], and stroke patients with COPD are at an increased risk of aspiration [ 25 ], which is a leading cause of death following a stroke.…”
Section: Introductionmentioning
confidence: 99%
“…However, no causal mechanism has been established between COPD and worse outcomes following a stroke. Heightened levels of systemic inflammation and oxidative stress may contribute to increased stroke severity and the occurrence of post-stroke adverse events [ 20 , 23 ]. It is difficult to determine the causal mechanisms that may explain worse outcomes following a stroke in human COPD.…”
Section: Introductionmentioning
confidence: 99%